2014
DOI: 10.1007/s00262-014-1555-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered chemokine production and accumulation of regulatory T cells in intestinal adenomas of APCMin/+ mice

Abstract: Tumor progression in the colon moves from aberrant crypt foci to adenomatous polyps to invasive carcinomas. The composition of the tumor-infiltrating leukocyte population affects the ability of the immune system to fight the tumor. T cell infiltration into colorectal adenocarcinomas, particularly T helper 1 (Th1) type T cells as well as increased regulatory T cell (Treg) frequencies, is correlated with improved prognosis. However, whether Th1 cells and Tregs are already present at the adenoma stage is not know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 52 publications
1
42
1
Order By: Relevance
“…Lamina propria cells from small intestinal mouse tumors and unaffected intestine were isolated as previously described [11, 30]. Briefly, epithelial cells were removed by HBSS medium containing EDTA, FCS, and HEPES.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lamina propria cells from small intestinal mouse tumors and unaffected intestine were isolated as previously described [11, 30]. Briefly, epithelial cells were removed by HBSS medium containing EDTA, FCS, and HEPES.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated and used for cDNA synthesis as previously described [11]. Each real-time PCR reaction mixture contained cDNA, Power SYBR Green master mix (Applied Biosystems) and oligonucleotide primers to detect CXCL9 (forward: 5′-GAC CTT AAA CAA TTT GCC CCA AG-3′, reverse: 5′-TCC TTC ACC CCC ATC TGC TGA ATC TGG-3′), CXCL10 (forward: 5′-GAA ATT ATT CCT GCA AGC CAA TTT-3′, reverse: 5′-TCA CCC TTC TTT TTC ATG TAG CA-3′), CXCL11 (forward: 5′-GCA GAT ATT GAG AAA GCC TCC A-3′, reverse: 5′-TGG GAT TTA GGC ATC GTT GT-3′) and 18S RNA (forward, 5′-CGG C-GT TAT TCC CAT GAC-3′, reverse, 5′-AAG TTT CAG CTT TGC AAC CA-3′).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Niho et al [16] have used the APC Δ1309 mouse model to confirm that APC gene mutations can inhibit the formation of small intestinal adenoid tumors when in a state of hyperlipidemia. Moreover, Akeus et al [17] have successfully set up an APC Min/+ knockout gene mouse model and identified the relationship between cancer-associated lymphocytes and the accumulation of gastrointestinal adenoma. They draw a preliminary conclusion that mutations and the deletion of APC Min/+ in Wnt signaling pathways may affect the development of lymphatic system tumors, the number of T cells and the accumulation of adenoma.…”
Section: Application Of the Transgenic Animal Model In Crc Researchmentioning
confidence: 99%